POLITICAL PRAGMATISM IN THE CONTEXT OF ISLAMIC LAW: THE RELEVANCE OF IBN TAYMIYYAH'S THOT TO MERITOCRACY AND THE INTEGRITY OF PUBLIC OFFICIALS - Ali Rif'an; Asila Maysa Fatihah; Agus Nilmada Azmi (STAI Asy-Syukriyyah, 2026)
Islamic political discourse frequently ignores the practical aspects of governance itself in favor of normative discussions about the ideal structure of the state. Taqiyuddin Ahmad ibn Taimiyah’s ideas provide a radical yet practical viewpoint amid the contemporary crisis of leadership and public official morality. The purpose of this article is to reconstruct Ibn Taimiyah’s idea of Siyasah Syar’iyyah, with a focus on the doctrine of the “strong and capable leader” (al-qawiy al-amin) as opposed to the “pious but weak leader.” This study examines Ibn taimiyah’s masterpiece, As-Siyasah as-Syar’iyyah fi Ishlah ar-Ra’i wa ar-Ra’iyyah, using a qualitative method with a historical hermeneutics approach. The finding show that Ibn Taimiyah desacralized the caliphate institution; according to him, a leader’s legitimacy is based on two meritocratic factors: technical skill (quwwah) and moral integrity (amanah), rather than just Quraysh ancestry or the formality of allegiance. This idea, which emphasizes that the state’s objective is the enforcement of legal justice rather than just religious symbolism, is highly relevant as a critique of transactional politics and nepotism in modern democracies.